Women's extreme seclusion during menstruation and children's health in Nepal. - Supriya Joshi; Yubraj Acharya (Public Library of Science (PLoS), 2022)
There is limited empirical evidence from low-income countries on the effects of women's seclusion during menstruation on children's health. The objective of the current study was to examine the association between women's extreme seclusion during menstruation and their children's nutritional status and health in Nepal. Using nationally representative data from the 2019 Multiple Indicator Cluster Survey, we examined the relationship between mother's exposure to extreme forms of seclusion during menstruation and anthropometric measures of nutritional status and health outcomes among children ages 5-59 months (n = 6,301). We analyzed the data in a regression framework, controlling for potential confounders, including province fixed effects. We assessed extreme seclusion during menstruation based on women's exposure to chhaupadi, a practice in which women are forced to stay away from home-in separate huts or animal sheds-during menstruation and childbirth. Mothers' exposure to extreme seclusion during menstruation was associated with 0.18 standard deviation lower height-for-age z-scores (HAZ) (p = 0.046) and 0.20 standard deviation lower weight-for-age z-scores (WAZ) (p = 0.007) among children. Analysis by the place of seclusion showed that the negative association was stronger when women stayed in animal sheds-0.28 SD for HAZ (p = 0.007) and 0.32 SD for WAZ (p<0.001)-than when they stayed in separate huts. Extreme seclusion was associated with higher incidence of acute respiratory symptoms but not with incidence of diarrhea, irrespective of the place of seclusion. Women's extreme seclusion during menstruation in Nepal has profound implications on the physical health of their children. Additional research is needed to ascertain potential mechanisms.